Analisis Komitmen Pada Tugas dalam Pembelajaran Matematika Siswa SMP - Agustina Sulistia Ningsih; Adi Ihsan Imami (Universitas Sarjanawiyata Tamansiswa, 2021)
Students have commitment to important tasks as a form of responsibility for themselves to be able to complete all assigments despite difficulties. The existence of a commitment to the task will be an independent learning experience to measure the extent to which students understand the material that has been learned. This study aims to describe commitment to tasks in learning mathematics. The subjects of this study were 20 students of class VIII-3 at SMP Negeri 1 Rancabungur. This type of research is qualitative with descriptive methods. The data collection technique used a questionnaire based on the commitment indicator on the task as many as 32 items. The results showed that the overall percentage was 42%, meaning that almost half of the students were committed to the task. The percentage obtained is still at a low point (<50)so that efforts are needed to increase commitment to the task so that students can create a sense of learning and practice to achieve good learning achievement.